SOME ISSUES OF REGIONAL SECURITY IN SOUTHEASTERN EUROPE - BABIĆ Marko (2011)
The South East Europe region, despite various past integration initiatives and regional cooperation, remains fragmented and politically unstable. The initiatives of the international community aimed at achieving stability and security in this part of Europe focus on supporting economic and social development, democratization of internal systems, building a civil society, establishing the rule of law, settling ethnic and territorial disputes by peaceful means, etc. attention to a number of activities undertaken in this region of Europe, the author of the article notes that the effectiveness and success of these initiatives will be the result of economic and financial support for the region and the acceleration of the process of joining European and Euro-Atlantic organizations, as well as institutions of the region's states. Examples are the two great political projects in Bosnia and Herzegovina and Kosovo. After all, the dilemma of the European Union is the effectiveness of its projects in this historically difficult region of Europe. The large fragmentation of the region significantly impedes regional cooperation between the countries of south-eastern Europe that could potentially become EU members. Integration with the European Union remains one of the few non-controversial issues of the main political forces in the countries of the region. Unfortunately, it has not resulted in increased cooperation in the region, but has diminished regional initiatives.